2007
DOI: 10.1183/09031936.00015507
|View full text |Cite
|
Sign up to set email alerts
|

Tracheal aspirate pH is alkaline in pre-term human infants

Abstract: The pH of sputum and exhaled breath condensate is abnormal in several pulmonary disorders. Though airway pH regulatory proteins may be abnormally expressed in human development, the tracheal aspirate pH of infants born prematurely has not been studied.Undiluted mid-tracheal aspirate samples were obtained on the first day of life from pre-term (23-30 weeks' gestation) and term (o37 weeks' gestation) infants for pH measurement; subsequently, pH was measured on days 7, 14 and 21 from the pre-term infants who rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 9 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…Our current data suggest that at ASL pH 6.9, acid secretion is low and the H + channel is likely closed. However, ASL pH has been found to alkalinize to values >7 (Fischer and Widdicombe, 2006), and extremes of >8 have been measured under certain conditions (England et al, 1999; Paget-Brown et al, 2007). Although the reason for an excessive alkalinization of the airways is not fully understood, it may be governed by CFTR-mediated HCO 3 − secretion into the ASL (Ballard et al, 1999; Thiagarajah et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Our current data suggest that at ASL pH 6.9, acid secretion is low and the H + channel is likely closed. However, ASL pH has been found to alkalinize to values >7 (Fischer and Widdicombe, 2006), and extremes of >8 have been measured under certain conditions (England et al, 1999; Paget-Brown et al, 2007). Although the reason for an excessive alkalinization of the airways is not fully understood, it may be governed by CFTR-mediated HCO 3 − secretion into the ASL (Ballard et al, 1999; Thiagarajah et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In a study of exhaled breath condensate, normal average pH was 7.65, which dropped in asthmatics to an average of pH 5.23, and extreme values of pH 4.5 to pH 8.5 were reported (49). In another study, the pH of the tracheal aspirate from neonates was found to be alkaline, ranging between 5.8 and 8.8 (50) and with average pH of 7.8. Bronchoalveolar lavage fluid sampled from neonates is on average acidic with a pH of 5.5 but ranges up to pH 7.5 during respiratory distress (51).…”
Section: Ph Gradientsmentioning
confidence: 96%
“…Over the past 15 years, acidification of EBC pH has been studied as a biomarker in a variety of diseases including asthma, [6,16,17] cystic fibrosis, [18,19] respiratory syncytial virus, [14] bronchpulmonary dysplasia, [20] and ARDS [21,22]. It is possible that the ability of the airway epithelium to acidify in response to various insults can be reflected through EBC pH [23][24][25].…”
Section: Introductionmentioning
confidence: 99%